ANALISIS GAYA KEPEMIMPINAN KETUA PANWASLU KECAMATAN GUNUNGSITOLI IDANOI DALAM TAHAPAN PEMILU TAHUN 2024 DI KECAMATAN GUNUNGSITOLI IDANOI - Zebua, Faevman Buala; Ndraha, Ayler B.; Mendrofa, Yupiter; Zebua, Emanuel (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract. The aims of this research are 1) To analyze the leadership style of the chairman of the Panwaslu sub-district of Gunungsitoli Idanoi in the 2024 election stages, 2) To analyze the leadership style applied by the chairman of the Panwaslu of Gungsitoli Idanoi sub-district in the 2024 election stages and 3) To analyze the efforts made take action to overcome obstacles and obstacles to the leadership style of the chairman of the Panwaslu, Gunungsitoli Idanoi sub-district in the 2024 election stages in Gunungsitoli Idanoi sub-district. Data analysis techniques use data reduction, data presentation and drawing conclusions. The research results show that 1) the leadership style of the Chair of the Panwaslu of Gunungsitoli Idanoi sub-district in the 2024 General Election stages is categorized as good, 2) the Chair of the Panwaslu of Gunungsitoli Idanoi sub-district applies a democratic leadership style and 3) The efforts made by the Chair of the Panwaslu of Gunungsitoli Idanoi sub-district in overcoming obstacles and barriers by The leadership style he applies is to proactively provide solutions and be firm and increase member discipline during plenary meetings so that decisions can be made quickly